Catalytic Activation of a Carbon–Chloride Bond by Dicationic Tellurium-Based Chalcogen Bond Donors - Steinke, Tim; Wonner, Patrick; Engelage, Elric; Huber, Stefan M. (Synthesis, 2021)
Noncovalent interactions such as halogen bonding (XB) and chalcogen bonding (ChB) have gained increased interest over the last decade. Whereas XB-based organocatalysis has been studied in some detail by now, intermolecular ChB catalysis only emerged quite recently. Herein, bidentate cationic tellurium-based chalcogen bond donors are employed in the catalytic chloride abstraction of 1-chloroisochroman. While selenium-based ChB catalysts showed only minor activity in this given benchmark reaction, tellurium-based variants exhibited strong activity, with rate accelerations of up to 40 relative to non-chalogenated reference compounds. In general, the activity of the catalysts improved with weaker coordinating counterions, but tetrafluoroborate took part in a fluoride transfer side reaction. Catalyst stability was confirmed via a fluoro-tagged variant.
Keywords: chalcogen bonding; organocatalysis; halide abstraction; Lewis acids; intermolecular interactions; noncovalent interactions